The breeding ecology of the Mute Swan Cygnus olor in central Poland - Wlodarczyk, R; Wojciechowski, Z (Wildfowl, 2001)
This paper describes the breeding performance of the Mute Swan in central Poland. Population size, productivity and possible factors affecting hatching success are discussed. During a four-year study (1997-2000), between 75-101 breeding pairs were found within the study area. Fishponds were the habitat most frequently used by swans in all seasons, and birds preferred small water bodies 15-25 ha) to large ones (>25 ha). The mean clutch size was 6.02 eggs, and the average number of cygnets fledged per pair was 4.42. Pairs that bred on small ponds had higher breeding success. Food availability within a territory was not correlated with productivity and the number of fledged cygnets did not appear to depend on the intensity of human activities at the site. However, the level of contact with non-territorial birds within breeding territories had a significantly negative effect on the breeding success of a pair.